Penelitian Tindakan Kelas untuk Meningkatkan Hasil Belajar Siswa Materi QS. At-tin melalui Problem Based Learning di SDIT Al- Fatih Mukomuko - Sri Rahayu Ningsih; Alfauzan Amin (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
This study aims to determine how much the improvement of student learning outcomes in Islamic religious education learning qs. at-tin through problem-based learning at sdit al- fatih mukomuko. Type of research researchers use class action research, researchers use class action research is with the aim of continuing to improve and improve learning strategies in the classroom. This research was conducted at SDIT AL-FATIH Mukomuko in 2023. The sample of this study was fifth-grade students totaling 20 students. Data collection techniques used by researchers in collecting data are interviews, questionnaires, observation, tests, and documentation. Data analysis researchers use student learning completeness scores. The stages in this study include three stages, namely (1) the planning stage; (2) the action stage; (3) the observation stage; and (4) the reflection stage. The results revealed that the application of Problem-Based Learning at SDIT AL-FATIH Mukomuko can improve student learning outcomes in reading the Koran (QS. At-tin) and can help interest in learning and student motivation.